Profiles of antibiotic resistance of microorganisms isolated from the droppings of healthy farm birds - S. B. Lysko; V. I. Pleshakova (International Journal of Veterinary Medicine, 2026)
Bird droppings, widely used as organic fertilizer in agriculture, pose a serious threat to human health and the environment due to the presence of antibiotic residues and antibiotic resistance genes. Litter monitoring for the presence of antibiotic-resistant bacteria is an urgent task to minimize the risks of spreading antimicrobial resistance in the environment. The aim of the study was to study the species composition and antibiotic resistance profiles of bacteria isolated from the droppings of healthy poultry at seven enterprises in the Siberian region. A study of 280 litter samples from healthy laying hens and broiler chickens of different ages was conducted. The indication of microorganisms was carried out by methods generally accepted in microbiology using simple and differential diagnostic nutrient media, identification to the species was carried out using the technology of matrix laser desorption ionization time-of-flight mass spectrometry (MALDI-ToF MS). Bacterial resistance was studied by the disco-diffuse method. The sensitivity of 550 isolated isolates to 26 antibacterial drugs of various pharmacological groups was studied. Based on research, it was found that the microbiocenosis of the litter of healthy chickens is dominated by bacteria of the Enterobacteriaceae family — 46,0 % (Escherichia coli, Proteus mirabilis) and Staphylococcaceae — 29,8 %. When studying their antibiotic resistance profiles, representatives of the opportunistic microflora from the Staphylococcaceae family showed the greatest resistance to the studied antibiotics: 95—100 % of the cultures were resistant to penicillins, fluoroquinolones, tetracyclines, macrolides and lincosamides, while in 100 % of cases they were polyresistant. Among the representatives of the Enterobacteriaceae family, over 50 % of Escherichia coli and Proteus mirabilis isolates were resistant to antibiotics from the penicillin and fluoroquinolone group, polyresistance was detected in 16,6 % and 13,3 % of cultures, respectively.